New Method for Fine Calculation of Bridge Temperature Field Based on BIM Solar Radiation Analysis - Yin-Gang Wang; Xiong-Jun He; Fang Ouyang; Jia He; Wei-Wei Wu; Chao Wu (Advances in Civil Engineering)
Fine calculation of bridge temperature fields is significant for accurately evaluating thermal actions in bridge structures. Determining thermal loads on bridge surfaces caused by solar radiation is the most challenging part of the numerical thermal analysis because the sunlit and shaded areas on bridge surfaces change continuously with the sun’s rotation. Existing methods have low accuracy in determining thermal loads and cannot be applied to complex bridges. This study presents a new method for calculating temperature fields based on the advantages of building information modeling (BIM) technology in solar radiation analysis (SRA) and information sharing. This method starts with obtaining an accurate hourly insolation distribution on bridge surfaces through SRA implemented in a BIM system. Then, a Python script seamlessly maps the insolation information to finite element surfaces as thermal loads. This paper details the new method’s implementation steps and technical details, and a practical application on a concrete box girder demonstrates its applicability and effectiveness. Compared with previous methods, the proposed method has significant advantages, such as a more accurate calculation for solar radiation, a lower technical threshold, a higher degree of automation, less computational time, and easier finite element modeling.